Management Fisioterapi Pada Kasus Post Operasi Histerektomi Total Akibat Mioma Uteri: Case Study - Nadya Aqsha Tamarinda; Adnan Faris Naufal; Galih Adhi Isak Setiawan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Uterine myoma or often called fibroids is a benign tumor originating from the smooth muscle of the uterus. Tumor cells are formed due to genetic mutations, then develop due to the induction of the hormones estrogen and progesterone. The incidence of uterine myoma in Indonesia ranks second after cervical cancer, the incidence of uterine myoma in Indonesia is found to be 2.39% - 11.70% in all patients with gynecological cases hospitalized. Hysterectomy is surgical removal of the uterus (uterus) is one of the procedures performed for uterine myoma. Physiotherapy aids recovery by avoiding or minimizing complications as well as providing physical rehabilitation to support the return of physical function postoperatively hysterectomy. Based on the results of the evaluation of interventions that have been given, breathing exercises, pelvic floor muscle training, active exercises on the hip to the lower extremities as well as early transfer and ambulation exercises have been shown to reduce pain levels, strengthen pelvic floor muscles thereby reducing incontinence, and increase functional activity.